Ułatwienia w prowadzeniu działalności gospodarczej w obszarze międzynarodowego obrotu towarowego wynikające z pakietu prawnego UKC. Wybrane aspekty - Laszuk, Mirosława (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The Union Customs Code, the delegated regulation, and the implementing regulation contain a wide array of facilitations for entrepreneurs trading in goods. The major role is played by the Authorized Economic Operator (AEO) and the Binding Tariff Information (BTI), which provide numerous benefits for the entities conducting the international trade in goods. Nevertheless, despite numerous advantages both institutions provide other solutions which are less beneficial for the entities enjoying them; for example, acomplicated audit procedure followed when issuing AEO permits, and “the prohibition on purchasing” Binding Tariff Information, which has been recently introduced.
Keywords: Authorised Economic Operator; Binding Tariff Information; entrepreneur